2021
DOI: 10.1186/s12913-021-07205-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of preventive behavior of nosocomial infections in nursing staff: a structural equation model based on the social cognitive theory

Abstract: Background The occurrence of nosocomial infections remains a health threat to patients and hospital staff. This study applied social-cognitive theory for predicting determinants of nosocomial infections control behaviors in hospital nursing Staff. Methods In this cross-sectional study, 280 nurses and assistant nurses were selected by random sampling from intensive care wards including CCU, ICU, NICU, dialysis of educational hospitals in Mashhad, Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…In other words, an individual's selfefcacy not only has a direct efect on task load but also has an indirect efect through extraneous cognitive load. ICU nurses with high-level self-efcacy are always able to cope with unexpected issues and come up with solving strategies [26,27]. Tese abilities weaken the high level of the extraneous cognitive load caused by unclear instructions for nursing activities in daily nursing practice, thereby reducing the task load in terms of mental demand, physical demand, temporal demand, performance, efort, and frustration for ICU nurses.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, an individual's selfefcacy not only has a direct efect on task load but also has an indirect efect through extraneous cognitive load. ICU nurses with high-level self-efcacy are always able to cope with unexpected issues and come up with solving strategies [26,27]. Tese abilities weaken the high level of the extraneous cognitive load caused by unclear instructions for nursing activities in daily nursing practice, thereby reducing the task load in terms of mental demand, physical demand, temporal demand, performance, efort, and frustration for ICU nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian terdahulu menunjukkan bahwa ketika emosi negatif seperti takut dan cemas rendah maka upaya prevensi meningkat (Meng et al, 2023;Rochira et al, 2022). Model kognitif sosial yang memasukkan efikasi diri dalam model pencegahan juga terbukti berperan besar (Lin et al, 2020;Mahdizadeh et al, 2021). Variabel-variabel dari dua pendekatan tersebut yang belum dimasukkan kiranya menjadi catatan tersendiri dari penelitian ini.…”
Section: Diskusiunclassified
“…16 Personal efficacy affects health behavior 11,13 directly and by its impact on outcome expectations, goal setting and self-regulation, and social support. The SCT has been widely used in predicting and explaining preventive behaviors, such as the physical activity of breast cancer patients, 17 hepatitis B virus vaccine acceptance, 18 health screening behaviors among those with type 2 diabetes, 19 and video intervention before referral based on SCT to increase screening mammography. 20 A review of the literature using the SCT identified self-efficacy as having a critical effect on an individual's participation in breast cancer screening.…”
Section: Study Frameworkmentioning
confidence: 99%
“…The results of this study indicate that goal setting and self-regulation play an important role in the breast cancer screening behavior of FDRs, which is in line with preventive behavior ▪ 277 of nosocomial infections in nursing staff. 18 The diagnosis of breast cancer in an FDR can motivate women to improve their health-related behavior. 35 Self-regulation begins with the adoption of a goal.…”
mentioning
confidence: 99%